WORKSHOP FOR THE UTILIZATION OF LASER AND TECHNOLOGY 4.0 TO USE THE FUNCTIONS OF THE PHYSICS LABORATORY FOR SMA, MA, AND SMK TEACHERS IN GRESIK DISTRICT - Retna Apsari; Moh Yasin; Samian; Herri Trilaksana; Supadi Supadi; Pujiyanto Pujiyanto (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Almost all of the development and research actors in the field of optical physics come from universities. Meanwhile, at the SMA, MA and SMK levels, this field is very poorly understood. This is due to the limited knowledge of optical physics and its supporting technology owned by the teachers. Objective: With this continuous and continuous training, it is hoped that it can provide new insights about understanding lasers and their use for technology 4.0 and can utilize laboratories in schools at the SMA, MA and SMK levels. Method: In practice, this activity was carried out virtually via Zoom which was attended by teachers at the SMA, MA and SMK levels, and was filled by several Physics lecturers at Airlangga University in delivering material in the form of lasers, laser diffraction, and 3D printing technology. Results: Partners get information related to increasing knowledge of the use of lasers and diffraction phenomena that can be conveyed and demonstrated to students, as well as the use of 3D printing technology so that teachers can convey and increase students' interest in learning Physics. Conclusion: Physics teachers at the SMA, MA and SMK levels, especially in Gresik Regency, feel quite helped by this activity because it has provided updated knowledge and information related to understanding and mastering the basic principles and applications of using lasers with a very satisfied level of satisfaction of about 47.73%, a satisfied category of about 45.27%, and the remaining 7% choosing to be less satisfied.